Carbon Nitride‐Based Photoanode with Enhanced Photostability and Water Oxidation Kinetics. (10th April 2021) - Karjule, Neeta; Singh, Chanderpratap; Barrio, Jesús; Tzadikov, Jonathan; Liberman, Itamar; Volokh, Michael; Palomares, Emilio; Hod, Idan; Shalom, Menny
Abstract: Carbon nitrides (CN) have emerged as promising photoanode materials for water‐splitting photoelectrochemical cells (PECs). However, their poor charge separation and transfer properties, together with slow water‐oxidation kinetics, have resulted in low PEC activity and instability, which strongly impede their further development. In this work, these limitations are addressed by optimizing the charge separation and transfer process. To this end, a nickel–iron based metal‐organic framework, Ni/Fe‐MIL‐53, is deposited, that acts as an oxygen evolution pre‐catalyst within the CN layer and incorporate reduced graphene oxide as an electron acceptor. Upon electrochemical activation, a uniform distribution of highly active oxygen evolution reaction (OER) catalysts is obtained on the porous CN surface. Detailed mechanistic studies reveal excellent hole extraction properties with high OER catalytic activity (83% faradaic efficiency) and long‐term stability, up to 35 h. These results indicate that the decrease in performance is mainly due to the slow leaching of the catalyst from the CN layer. The CN photoanode exhibits a reproducible photocurrent density of 472 ± 20 µA cm −2 at 1.23 V versus reversible hydrogen electrode (RHE) in 0.1 m KOH, an exceptionally low onset potential of ≈0.034 V versus RHE, and high external quantum yield. Abstract : Here, a carbon nitride (CN) photoanode with Ni/Fe–(oxy)hydroxide is shown as a cocatalyst with state‐of‐art photoelectrochemical performance thanks to superb water oxidation kinetics (reaching 83% faradaic efficiency for oxygen evolution), hole extraction properties, low onset potential, and good long‐term stability (up to 35 h). These findings position CN‐based materials as cheap, efficient, and stable photoanode active layers for water‐splitting photoelectrochemical cells.